Analysis the efficiency of multi-input-multi-output (MIMO) transmit receive systems - Ali Hlal Mutlaq; Mohammed Ayad Saad; Faris Hassan Tata; Ghanim Thiab Hasan (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Transmit antennas are chosen in multi-input-multi-output (MIMO) systems. Effective in improving system capacity while lowering RF connection costs and simplifying the system. Complete method with greatest accuracy for joint transmits and receive antenna selection (JTRAS), capable of scanning all subsets of both transmitting and receiving antennas for the optimal solution. However, when as the number of antennas but also computational complexity increase grows too great, limiting its application. Antennas are coded fractionally channel capacity maximizing coding is used as a basic criterion in this paper, and an intelligent algorithm Particle swarm algorithm, generic algorithm are used to pick antennas. The simulation results show that both algorithms are capable of performing antenna selection.